Dietary guanidinoacetic acid supplementation improves rumen metabolism, duodenal nutrient flux, and growth performance in lambs - Zhang, Shiqi; Yimamu, Mireguli; Ma, Chen; Pan, Jun; Wang, Caidie; Cai, Wenjie; Yang, Kailun (Frontiers in Veterinary Science, 2025)
Guanidinoacetic acid (GAA) is the only precursor of creatine, which is an important energy source for growth and metabolism. The degradation of guanidinoacetic acid in rumen plays a decisive role in its application in ruminant diet. Two experiments were conducted to investigate the rumen GAA escape rate and its effects on metabolism, blood metabolites and growth performance of Kazakh male lambs. In the first part of the experiment, 24 Kazakh male lambs equipped with rumen and duodenal fistulas were selected to determine the rumen escape rate of guanidylacetic acid. In the second part, 24 healthy Kazakh male lambs were selected to determine the growth performance. They were divided into 4 groups and fed a basal diet supplemented with 0, 500, 1,000, 1,500 mg/kg GAA, respectively. The results show that ruminal escape rates of 36–56% were achieved in lambs with dietary GAA supplementation at 500–1,500 mg/kg DM. Dietary 1,500 mg/kg DM GAA increased levels of creatine, IGF-I and insulin, and promoted lamb growth.